What makes health systems resilient against infectious disease outbreaks and natural hazards? Results from a scoping review - Jennifer B. Nuzzo; Diane Meyer; Michael Snyder; Sanjana J. Ravi; Ana Lapascu; Jon Souleles; Carolina I. Andrada; David Bishai (BMC, 2019)
Abstract Background The 2014-2016 Ebola outbreak was a wake-up call regarding the critical importance of resilient health systems. Fragile health systems can become overwhelmed during public health crises, further exacerbating the human, economic, and political toll. Important work has been done to describe the general attributes of a health system resilient to these crises, and the next step will be to identify the specific capacities that health systems need to develop and maintain to achieve resiliency. Methods We conducted a scoping review of the literature to identify recurring themes and capacities needed for health system resiliency to infectious disease outbreaks and natural hazards and any existing implementation frameworks that highlight these capacities. We also sought to identify the overlap of the identified themes and capacities with those highlighted in the World Health Organization's Joint External Evaluation. Sources of evidence included PubMed, Web of Science, OAIster, and the websites of relevant major public health organizations. Results We identified 16 themes of health system resilience, including: the need to develop plans for altered standards of care during emergencies, the need to develop plans for post-event recovery, and a commitment to quality improvement. Most of the literature described the general attributes of a resilient health system; no implementation frameworks were identified that could translate these elements into specific capacities that health system actors can employ to improve resilience to outbreaks and natural hazards in a variety of settings. Conclusions An implementation-oriented health system resilience framework could help translate the important components of a health system identified in this review into specific capacities that actors in the health system could work to develop to improve resilience to public health crises. However, there remains a need to further refine the concept of resilience so that health systems can simultaneously achieve sustainable transformations in healthcare practice and health service delivery as well as improve their preparedness for emergencies.